2001
DOI: 10.1046/j.1365-2036.2001.01126.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of NSAIDs on cryoprobe‐induced gastric ulcer healing in rats

Abstract: The administration of traditional NSAIDs is associated with a three-fold increase in the risk of development of signi®cant gastrointestinal complications, depending on previous risk factors. 1±3 Cross-sectional studies indicate that gastric or duodenal ulcers are present in 10±25% of patients on long-term NSAIDs.2, 4, 5 Most NSAIDinduced ulcers heal spontaneously without treatment, with or without discontinuation of NSAID therapy. 6 However, a small proportion of the ulcers produced by NSAIDs progress to clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…The mechanisms associated with GU healing and repair include epithelial cell proliferation, growth control, epidermal growth factors, angiogenesis and inhibition of acid secretion [12, 13, 28, 29]. Although our original hypothesis was that cell hyperproliferation in IM might influence GU healing, we found that there was no significant difference in cell proliferation Ki-67 stain index between the IM group and the no IM group.…”
Section: Discussionmentioning
confidence: 74%
“…The mechanisms associated with GU healing and repair include epithelial cell proliferation, growth control, epidermal growth factors, angiogenesis and inhibition of acid secretion [12, 13, 28, 29]. Although our original hypothesis was that cell hyperproliferation in IM might influence GU healing, we found that there was no significant difference in cell proliferation Ki-67 stain index between the IM group and the no IM group.…”
Section: Discussionmentioning
confidence: 74%
“…However, literature data on celecoxib are conflicting. For instance, Tibble et al (2001) found that celecoxib, administered for 6 days at 9 mg/kg/day, delayed ulcer healing in rats. Likewise, a 15-day treatment with celecoxib at 1.8 mg/kg twice daily impaired ulcer repair in rats (Berenguer et al, 2002).…”
Section: Nsaid-activated Gene and Gastric Ulcer Healing 147mentioning
confidence: 99%
“…Gastric mucus, gastric mucosal blood flow (GMBF) and mucosal PGE 2 Gastric mucus was determined according to the previous method [17] with a slight modification. Briefly, stomach was cut along lesser curvature.…”
Section: Gastric Secretionmentioning
confidence: 99%
“…NSAIDs 206 are one kind of the most frequently used drugs world wide [1], aspirin is one of them. Cross-sectional studies indicate that gastric or duodenal ulcers are present in 10-25% of patients on long-term NSAIDs [2]. Furthermore, continuing usage of NSAIDs often results in the recurrence of gastric ulcer [3].…”
Section: Introductionmentioning
confidence: 99%